Методика параметрического описания входных данных для расчета радиационного распухания ВКУ ВВЭР-1000 - Мирзов, И.В.; Кандала, С.М. (Ядерна та радіаційна безпека, 2016)
Разработана методика параметрического описания полей объемных тепловыделений при γ-разогреве и скорости набора радиационной дозы в выгородке ядерного реактора ВВЭР-1000 для упрощенных расчетных оценок стационарной температуры, радиационного распухания и напряженно-деформированного состояния конструкции. Методика основана на аппроксимации полей входных данных полиномами n-й степени по радиальной и окружной координатам. Погрешность результатов расчетов по данной методике не превышает 33 %, что позволяет применять методику для первичных оценок технического состояния внутрикорпусных устройств реакторов ВВЭР-1000. Розроблено методику параметричного опису полів об’ємних тепловиділень під час γ-розігріву та швидкості набору радіаційної дози у вигородці ядерного реактора ВВЕР-1000 для спрощених розрахункових оцінок стаціонарної температури, радіаційного розпухання й напружено-деформованого стану конструкції. Методика заснована на апроксимації полів вхідних даних поліномами n-го ступеня за радіальною та коловою координатами. Похибка результатів розрахунків за даною методикою не перевищує 33 %, що дозволяє застосовувати методику для первинних оцінок технічного стану внутрішньокорпусних пристроїв реакторів ВВЕР-1000. Ukraine currently does not have a company to perform full neutronic calculations of VVER-1000 core. In this regard, the paper proposes a method of parametric assignment of volumetric heating due to gamma-radiation and the irradiation dose rate in VVER-1000 core baffle. The method significantly simplifies assessment of the stationary temperature, irradiation swelling and stress-strain state of pressure vessel internals. The method is based on the approximation of the input fields by polynomial s of nth degree in the radial and circumferential coordinates. Methodical error in the calculation of the stationary temperature field is 3,2 %, 12,7 % — in the calculation of radiation swelling, 33,0 % — in the evaluation of radial deformations of the core baffle. This allows to use the method for the preliminary assessment of technical condition of the VVER-1000 reactor internals.